Globalization and high-risk systems. Issue 1 (2nd January 2017) - Le Coze, Jean-Christophe
Abstract: The argument of this paper is that globalization has reconfigured the landscape and operating constraints of high-risk systems. This article helps describe how the operating conditions of high-risk systems have been evolving over the past 30 years. In order to do so, findings from the literature on globalization, organization, regulation, multinationals, safety and disasters are considered and linked into an integrative framework. The article has three parts. First, the literature on globalization is introduced. It is shown that it constitutes a central feature of our time, but that this new historical moment is far from being unambiguous in its nature, implications and consequences. It is contested terrain that has given rise to a variety of interpretations. Second, the article discusses the extent to which safety as a field of research has acknowledged this new situation, concluding that it should be further explored. I argue that issues discussed in the field, such as 'outsourcing' or 'standardization', along with 'financialization', 'digitalization' or 'self-regulation' should be linked to the broader pattern of globalization. Third, this statement is empirically illustrated, building on the extensive writings about BP as an example of the failure of a globalized multinational. It is shown that BP's series of disasters between 2005 and 2010 can only be meaningfully understood in the context of a multinational shaping and being shaped by globalization. BP is the paradigmatic example of a new industrial safety era.